Analisis Yuridis Terhadap Pembiayaan Berbasis Kekayaan Intelektual dalam Ekosistem Ekonomi Kreatif di Indonesia - Shabillia, Larasta; Santoso, Budi (Fakultas Syariah INSURI Ponorogo, 2023)
The creative economy is one sector that has potention to continue to be developed, along with the lack of availability of natural resources to be exploited. The government started to pay attention to the creative economy by establishing a provision in the form of Law Number 24 of 2019 concerning the Creative Economy. As regulated in PP No. 24 of 2022, the existence of an intellectual property-based lending system requires several parties to regulate intellectual property as collateral. Regarding the implementation of binding guarantees in the form of property rights debt, property rights procedures, and technical implementation in its enforcement, some need to be regulated further. In addition, financial institutions may be concerned about credit to creative economy actors because there are no clear rules at this time. This research method uses library research methods with a normative legal approach. The results of this study are the extraordinary potential of Indonesia's creative economy has not been able to develop optimally because the awareness of creative actors about the value of the creative economy has not been maximized, there is no synergy, coordination, and implementation related to intellectual property-based creative economy financing between government sectors to overcome economic creative problems.